Distribution of Ocular Biometry and Intraocular Lens Power in Patients Undergoing Cataract Surgery in an Eye Camp in Northern Pakistan: Doi: 10.36351/pjo.v40i4.1770 - Shahid, Erum; Jafri, Asad Raza; Fasih, Uzma (Pakistan Journal of Ophthalmology, 2024)
Purpose: To report ocular biometric data of patients undergoing cataract surgery in an eye camp in a city of Northern area of Pakistan. Design: Cross-sectional descriptive study. Place and Duration of Study: A surgical eye camp was set up in the month of September 2022 for 6 days in a private hospital in Skardu. Methods: A total of 119 patients were selected with a non-probability consecutive sampling technique. Ocular biometry of permanent local residents with significant cataractswas included. Incomplete biometry data and coexisting diseases like corneal opacity, pterygium, and severe dry eye causing errors in biometry were excluded. Keratometry was done with an automated refractor-keratometer. Axial length was calculated with an A-scan (ultrasound contact method) and intraocular lens (IOL) power was calculated. Results: A total of 119 patients were selected for biometry among 3908 individuals visiting an eye camp. The mean axial length was 22.13 ± 1.25 SD mm. The mean keratometry readings (K1) was 43.28 ± 1.83 Diopter and (K2) 44.26 ± 1.67 D. The mean intraocular lens (IOL) power was 24.78 ± 3.43 D. The mean K readings were more in males as compared to females (p-value <0.005). There was no significant difference in axial length and IOL power among genders. Conclusion: This study gives normative data on ocular biometric parameters of patients undergoing cataract surgery at high altitudes in Skardu, Pakistan. These biometric values can be used as reference values in the local population